Dynamics Analysis of Spatial Parallel Mechanism with Irregular Spherical Joint Clearance - Xiulong Chen; Yuewen Li (Shock and Vibration)
Clearances caused by machining accuracy and assembly requirements are regular, but they will be irregular due to the wear of the kinematic pairs. At present, there are few studies on wear of space kinematic pairs. In order to grasp the effect of irregular spherical joint clearance after wear on the dynamic response, a method for solving irregular clearance problems based on the Newton–Euler method is proposed, and the dynamic response of 4-UPS-UPU spatial parallel mechanism with irregular spherical joint clearance is investigated. The kinematic model and contact force model of the clearance of the spherical joint are derived. The dynamic model of the mechanism with spherical joint clearance is established by the Newton–Euler method. Based on the Archard model, the three-dimensional dynamic wear model for spherical joint with clearances is developed. The wear depth and wear position of the spherical joint are obtained by the numerical solution. The method of reconstructing the geometric morphology after wear is proposed based on the finite element thought. The solution of the irregular clearance problem is put forward, and the dynamic response of the mechanism after wear is also analyzed. The results show that the dynamic response curves of the mechanism fluctuate around the ideal curves whether before wear or after wear. Compared with the regular clearance before wear, the results of the irregular clearance after wear have a greater impact on acceleration and contact force, and the vibration of the acceleration and contact force curve become more intense than before. Moreover, the displacement, velocity, and acceleration curves of the irregular clearance show some hysteresis than that before wear. Therefore, it can be inferred that the irregular clearance has more adverse effects on the mechanism and aggravates the wear between the elements of the kinematic joint; in addition, the stability and the reliability of the mechanism can be reduced.